The early posterior cortex pixel value ratio: a novel reliable indicator for distraction osteogenesis - Liu, Ze; Liu, Qi; Wang, Min; Zhou, Chenhan; Guo, Hongbin; Liang, Jieyu; Zhang, Yi (Frontiers in Surgery, 2023)
Aims We aimed to explore the associations of the early PVR in four cortices with Healing Index (HI), Lengthening Index (LI), and External Fixator Index (EFI) in the bone union and non-union groups. Methods A total of 52 patients, including 39 bone union and 13 bone non-union subjects, were recruited in this study. The general characteristics and PVR in four cortices in each group were explored. Afterward, the early PVR in four cortices, including medial, lateral, anterior, and posterior sides, were compared. Finally, the associations of the early PVR in four cortices with HI, LI, and EFI were also investigated. Results The general characteristics of these patients were consistent, except for HI (31.54 ± 12.24 vs. 45.08 ± 27.10, P = 0.018) and EFI (57.63 ± 18.15 vs. 71.29 ± 24.60, P = 0.046). The growth of regenerated callus was asymmetrical in the bone union group (the posterior PVR seems to grow faster), whereas no statistical difference was obtained in the bone non-union group. Furthermore, the posterior PVR in the bone union group was significantly higher than that in the bone non-union group (the first month: 0.96 ± 0.17 vs. 0.86 ± 0.06, p = 0.047; the second month: 0.98 ± 0.14 vs. 0.89 ± 0.09, p = 0.041; the third month: 1.00 ± 0.12 vs. 0.92 ± 0.09, p = 0.039). Most importantly, the posterior PVR was inversely associated with HI, LI, and EFI (the first month: r = −0.343, p = 0.041; r = −0.346, p = 0.042; r = −0.352, p = 0.041; the second month: r = −0.459, p = 0.004; r = −0.277, p = 0.101; r = −0.511, p = 0.002; the third month: r = −0.479, p = 0.003; r = −0.398, p = 0.018; r = −0.551, p = 0.001) in the bone union group, respectively. However, this finding was lost in the bone non-union group. Conclusion The early posterior cortex PVR seems to grow faster than the medial, lateral, and anterior sides in the bone union group, which represents an asymmetrical development pattern. Moreover, the posterior cortex PVR was negatively associated with HI, LI, and EFI, respectively. The posterior cortex PVR may be a novel and reliable detection index in the process of DO.